2023
DOI: 10.3390/ijms241612580
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mitochondrial Dysfunction and Idebenone Responsiveness in Fibroblasts from Leber’s Hereditary Optic Neuropathy (LHON) Subjects

Abstract: Leber’s hereditary optic neuropathy (LHON) is a disease that affects the optical nerve, causing visual loss. The diagnosis of LHON is mostly defined by the identification of three pathogenic variants in the mitochondrial DNA. Idebenone is widely used to treat LHON patients, but only some of them are responders to treatment. In our study, we assessed the maximal respiration rate (MRR) and other respiratory parameters in eight fibroblast lines from subjects carrying LHON pathogenic variants. We measured also the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Regarding the mtDNA copy number, Giordano et al observed that symptomatic carriers have a decreased rate of mtDNA copy number [ 5 ]. Baglivo et al correlated, in their study, the amount of mtDNA and treatment response and hypothesized that in m.3460G>A variant a protective role of mitochondrial biogenesis could be considered since in m.11778G>A variant, there was no correlation between the mtDNA copy number and disease penetrance [ 6 ]. In our study, we obtained a good response to Idebenone in patient with m.3460G>A mutation and no response in patient with m.11778G>A mutation.…”
mentioning
confidence: 99%
“…Regarding the mtDNA copy number, Giordano et al observed that symptomatic carriers have a decreased rate of mtDNA copy number [ 5 ]. Baglivo et al correlated, in their study, the amount of mtDNA and treatment response and hypothesized that in m.3460G>A variant a protective role of mitochondrial biogenesis could be considered since in m.11778G>A variant, there was no correlation between the mtDNA copy number and disease penetrance [ 6 ]. In our study, we obtained a good response to Idebenone in patient with m.3460G>A mutation and no response in patient with m.11778G>A mutation.…”
mentioning
confidence: 99%